Positive correlation between environmental PM2.5 and blood lead levels in patients undergoing maintenance hemodialysis - Chen CY; Liu MH; Hsu CW; Weng CH; Yen TH; Huang WH (Therapeutics and Clinical Risk Management, 2017)
Chao-Yu Chen,1,2,* Ming-Hui Liu,3,* Ching-Wei Hsu,1,2 Cheng-Hao Weng,1,2 Tzung-Hai Yen,1,2 Wen-Hung Huang1,2 1Department of Nephrology and Division of Clinical Toxicology and Toxicology Laboratory, Chang Gung Memorial Hospital, Linkou Medical Center, Taoyuan, Taiwan, Republic of China; 2Chang Gung University College of Medicine, Taoyuan, Taiwan, Republic of China; 3Department of Pediatric Dentistry, Chang Gung Memorial Hospital, Tao-Yuan, Taiwan, Republic of China *These authors contributed equally to this work Abstract: Patients undergoing hemodialysis (HD) have significantly higher mean blood lead levels (BLLs) than those in healthy individuals. Because elementary lead can be found in particulate matter with a diameter of <2.5 µm (PM2.5), this cross-sectional study was conducted to assess the effect of environmental PM2.5 exposure and other clinical variables on BLLs in patients receiving HD. We recruited 921 patients on maintenance HD (MHD) who had undergone HD for at least 6 months and who had previously participated in a BLL study. Mean PM2.5 concentrations in living environments in the previous 12 and 24 months were analyzed using a blood lead test. From a multivariate analysis, after adjustment for related factors, the mean PM2.5 concentrations in the previous 12 and 24 months were positively associated with log BLLs. In addition, days with PM2.5 levels exceeding the standard level during the previous 12 and 24 months were positively associated with log BLLs. Patients exposed to higher PM2.5 concentrations and more days with PM2.5 levels exceeding the standard level exhibited a higher prevalence of high and high-normal BLLs and a lower prevalence of low-normal BLLs. After adjustment for related variables, the BLLs exhibited a significantly positive association with environmental PM2.5 in patients undergoing MHD. Keywords: air pollution, particulate matter, PM2.5, lead, hemodialysis